KAJIAN MINAT BELANJA ONLINE PAKIAN READY TO WEAR PLUS-SIZE - Krishna Wardhani (Universitas Ciputra Surabaya, 2021)
It is very important for a clothing brand, have a clear understanding about their target market. Clothing brands in Indonesia are starting to look at plus-size women as a potential growing market, especially for online shopping. One brand must pay attention to both products and the online shop. It is essential for a clothing brand to have their own online shop service in this day and age, especially for clothing brands that have a particular target market, such as the plus-size women. Based on previous research, the plus-size women are starting to lose their interest in online shopping because of the unfulfilled expectations in designs, size precision, quality as well as the online shopping experience itself. We were using two research methods, by spreading questionnaires and direct interviews. We gathered information from 79 responders of plus-size women with clothing size starting from XXL and larger, age range between 26 to 40+ years old at 23 -25 July 2020. We used two techniques, SPSS and The Rank Spearman & Kendall Tau method. SPSS are used to process the quantitative data to find the correlation between the clothing designs, sizes, and quality as well as the shopping experience. The Rank Spearman and Kendall Tau method are used for the correlation tests. There are several results. There is a relationship between the variables of design, size, quality, and a positive shopping experience however, quality falls into a very weak category. Body shape can be the basis for determining the design and size of the products. Several factors, such as colors, patterns, and materials, are in accordance with the desires of plus-size consumers. There is a greater chance of using the pre-order system. Optimization of websites that are used as showcases by using educational content on clothing styling and standardization of product specifications in order to create high engagement so as to foster customer trust. Further studies need to prove the efficiency of the user interface in accordance with the design recommendations. Keywords: ready to wear; plus-size; consumer’s shopping interests; online shopping